2017
DOI: 10.15544/mts.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic and Eudaimonic Values in Sport Participation of the Youth

Abstract: The aim of this study is to present the hedonic and eudaimonic value preferences for the youth Lithuanian participants and non-participants in sport. Participants of this study were 345 school children, 16–18 years of age. Self-report questionnaire consisted of S. H. Schwartz’s Value Survey, questions about socio-demographic characteristics, information about activity in sports and questions about expectations of the career in sport. The results revealed that eudaimonic values are more expressed in females tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(50 reference statements)
0
1
2
Order By: Relevance
“…Other values such as Tradition, Self-Direction, Stimulation, Hedonism, and Benevolence are rated higher by regular respondents rather than athletes. Our results do not agree with the data obtained in other works, in particular, with the Latvian study, where on the contrary it was athletes who had higher scores on Hedonism, Stimulation, Self-Direction and Achievement (Sigitas et al, 2017). Differences in the results are most likely due to the heterogeneity of the sample, which included representatives of different sports.…”
Section: Resultscontrasting
confidence: 99%
“…Other values such as Tradition, Self-Direction, Stimulation, Hedonism, and Benevolence are rated higher by regular respondents rather than athletes. Our results do not agree with the data obtained in other works, in particular, with the Latvian study, where on the contrary it was athletes who had higher scores on Hedonism, Stimulation, Self-Direction and Achievement (Sigitas et al, 2017). Differences in the results are most likely due to the heterogeneity of the sample, which included representatives of different sports.…”
Section: Resultscontrasting
confidence: 99%
“…The result of our study does not agree with the data presented in the study by Daukilas et al (2017).…”
Section: Cross-group Differences In the Assessment Of Basic Valuescontrasting
confidence: 99%
“…It was found that sports are negatively correlated with the preference for materialistic values, such as power, wealth, money, and positively correlated with such values as true friendship, creativity, free time, diverse life. In a study conducted in Lithuania, it was found that young people involved in sports appreciate the value of achievement, hedonism, self-regulation, stimulation, conformity and security higher than young people not involved in sports (Daukilas, Kovalčikienė, & Balakienė, 2017).…”
Section: Problem Statementmentioning
confidence: 98%